Fish vertebrae as archeological biomarkers of past marine ecological conditions: Comparison of mercury levels in Chilean swordfish between the Middle Holocene and the modern period. (17th October 2021) - Biton‐Porsmoguer, Sebastian; Bouchoucha, Marc; Marco‐Miralles, Françoise; Salazar, Diego; Béarez, Philippe
Abstract: The ocean has always been a source of inspiration for past and present civilizations, especially for those involved in fishing activities. The regular fishing of large pelagic fish by past societies using harpoons has been demonstrated, with several studies reporting the discovery of an important fishery of large pelagic fish (including swordfish) dating from as early as the sixth millennium BCE on the North Chilean Pacific Coast. The swordfish ( Xiphias gladius ) is a cosmopolitan, highly migratory species found in all warm and temperate oceans and seas, and mercury is known to bioamplify along food webs, increasing with the trophic level of organisms up to these top predators. This study, therefore, analyzes and compares the mercury levels of archeological and modern vertebrae in swordfish. The archeological fish remains were recovered during excavation of the Zapatero archeological site on the northern coast of Chile, and the modern vertebrae were collected from specimens caught in the Pacific Ocean. The archeological vertebrae showed lower levels of mercury in comparison with those of current individuals, despite their larger size. However, the elevated Hg levels in archeological vertebrae proved the presence of naturally occurring mercury in the mid‐Holocene. Analyses on modern vertebrae confirmed the anthropic origin of mercury in the marine food web. Mercury biomagnifies through the marine food chain to swordfish (and humans) and did so even during the Holocene (bioaccumulation phenomenon). This study evidences that vertebrae and bones are potentially good biomarkers of mercury, including for archeological fish remains, and that the possible harmful effects on the health of past human communities can be analyzed and explained by the high consumption of fish.